Content-Analysis of the Concept «Monitoring» - Ganna Krasil’nykova (Pedagogical Discourse, 2013)
In the article elucidates the dynamics of including of the concept «monitoring» in term systems of different sciences, its transterminologization in pedagogics and analysis of maintenance of the concept for its effective use in educational practice. The executed kontent-analysis of concept «monitoring» is after semantic categories: family word, substancional and functional signs, object and result. It is set that comparison of maintenance of monitoring concept is complicated, as come forward the family macrocomponents of monitoring: supervision as method of research of the material world, control as process, system of operations and procedures; thus the specific signs of monitoring is him permanent and continuous character.